Withdrawn and wired: Problematic internet use accounts for the link of neurotic withdrawal to sleep disturbances - Herlache, Anne Danielle; Lang, Kathryn M.; Krizan, Zlatan (Sleep Science, 2018)
Although neuroticism is the strongest personality predictor of sleep disturbance, it is not clear whether dysphoric (Withdrawal) or angry (Volatility) aspect of neuroticism is more important and whether problematic technology use plays an intervening role. To this end, this study examined distinct contributions of neurotic withdrawal and volatility in predicting self-reported sleep disturbance while testing the mediating role of problematic internet use. Methods: One-hundred and fourty-three college students completed an online survey that included measures of neuroticism, sleep quality, and problematic internet use. Results: Although both aspects of neuroticism predicted poor sleep, Withdrawal emerged as a stronger and the only unique predictor. Furthermore, problematic internet use explained a portion of Withdrawal’s relationship to worse sleep, especially nighttime and daytime disturbances. Discussion: The findings suggest that dysphoric rather than angry features of neuroticism are more important for sleep problems and that the problematic use of modern technology may be an important contributing factor.
Keywords: Sleep Wake Disorders; Sleep; Internet; Personality